Comparative thermoregulatory physiology of two dunnarts, Sminthopsis macroura and Sminthopsis ooldea (Marsupialia:Dasyuridae) - Tomlinson, Sean; Withers, Philip; Maloney, S. (CSIRO Publishing, 2012)
Metabolic rate and evaporative water loss (EWL) were measured to quantify the thermoregulatory patterns of two dasyurids, the stripe-faced dunnart (Sminthopsis macroura) and the Ooldea dunnart (S. ooldea) during acute exposure to T a between 10 and 35°C. S. macroura maintained consistent T b across the T a range, whereas S. ooldea was more thermolabile. The metabolic rate of both species decreased from T a=10°C to BMR at T a=30°C. Mass-adjusted BMR at T a=30°C was the same for the two species, but there was no common regression of metabolic rate below the thermoneutral zone (TNZ). There was no significant difference between the species in allometrically corrected EWL at T a=30°C. Total EWL increased significantly at T a=10 and 35°C compared with the TNZ for S. macroura, but was consistent across the T a range for S. ooldea. At any T a below the TNZ, S. macroura required more energy per gram of body mass than S. ooldea, and had a higher EWL at the lower critical T a. By being thermolabile S. ooldea reduced its energetic requirements and water loss at low T a. The more constant thermoregulatory strategy of S. macroura may allow it to exploit a broad climatic envelope, albeit at the cost of higher energetic and water requirements. Since S. ooldea does not expend as much energy and water on thermoregulation this may be a response to the very low productivity, 'hyperarid' conditions of its central Australian distribution. © 2012 CSIRO.